Complementary medicine usage in surgery: a cross-sectional survey in Germany - Lederer, Ann-Kathrin; Samstag, Yvonne; Simmet, Thomas; Syrovets, Tatiana; Huber, Roman (BMC complementary medicine and therapies, 2022)
Complementary medicine (CM) is frequently used by patients, but little is known about the usage of CM in surgical patients. The study aimed to elucidate the relevance of CM in surgery.
Gesehen am 22.12.2022